Musical Formation in Al-Mutanabbi’s Poetry "The Grammatical Level as a Model" - حسين محمّد; مصطفى نمر; وهران حبيب (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research deals with the musical composition in Al-Mutanabbi’s poetry by shedding light on the grammatical level. Which appeared clearly in his poetry, and is closely related to the poet’s psyche and the structure of his life, as the grammatical construction of the linguistic vocabulary is based on a number of stylistic choices for one article over another and for one linguistic formulation over the other, which ultimately reveals the secret of the poet’s tendency to this stylistic pattern and not to others. The research also tries to identify the grammatical level, which was represented in the two techniques of intonation and repetition. Intonation in which we defined the definition linguistically and idiomatically, then we talked about its types and functions, then the repetition that we dealt with its definition linguistically and idiomatically, then we talked about the types of repetition contained in the repetition of the letter, the repetition of the name, and the repetition of sentences and syllables, then we joined the theoretical presentation with analyzed models that show the extent of Al-Mutanabi’s use These two techniques, and to know the extent of their impact on the construction of the poetic text.